Estudio de la factibilidad para la creación de un departamento de exportaciones en el cabildo indígena de suba para la exportación de artesanías a Alemania. (2020)
Colombia has a large number of artisans from various parts of Colombia, who over time have created unique and special pieces, with techniques at hand, learned from their ancestors, but the great problem that artisans who are part of the Muisca indigenous community of suba, is the lack of support and lack of knowledge so that these unique and differentiated pieces can reach international markets. Handicrafts are a great source of employment in Colombia, since year after year they have gone from informality to formality, and thanks to this, growth in exports has been achieved, being these handicrafts highly desired abroad. ProColombia and the Chamber of Commerce have supported a business conference, which is held annually, in which international businessmen participate, in order for artisans to be recognized, and thus ensure that their products are increasingly sought after internationally. Approximately 2,000 Colombian entrepreneurs from different departments and approximately 1,000 foreign entrepreneurs meet in these macro wheels.